Clozapine Induced Ogilvies Syndrome - Mosli, Ahmoud Hisham; Beaton, Melanie (Journal of Medicine, 2012)
We report a case of clozapine induced acute intestinal pseudo obstruction (also known as Ogilvies syndrome) in a 54-year female with a history significant for multiple psychiatric disorders. The diagnosis was made after a challenging clinical presentation where collaboration between multiple medical services resulted in reaching a unified diagnosis. The diagnosis was established based on multiple radiological imaging modalities and confirmed by a documented response to colonic decompression through colonoscopy and discontinuation of the offending medication. DOI: http://dx.doi.org/10.3329/jom.v13i2.12769 J Medicine 2012; 13 : 237-239